Mediterranean Diet Combined With a Low-Carbohydrate Dietary Pattern in the Treatment of Overweight Polycystic Ovary Syndrome Patients - Mei, Shanshan; Ding, Jie; Wang, Kaili; Ni, Zhexin; Yu, Jin (Frontiers in Nutrition, 2022)
Objectives: The aim of this study is to determine the therapeutic effect of a Mediterranean diet (MED) combined with a low-carbohydrate (LC) dietary model in overweight PCOS patients. Methods: In this 12-week randomized controlled clinical trial, 72 overweight patients with PCOS were randomly assigned to one of two energy-restricted dietary models: the MED/LC diet or the LF diet. After the intervention, the number of the two groups returned to normal menstruation was counted. Body weight, BMI, WHR, body fat percentage (BF%), FINS,FPG, HOMA-IR, QUIKI,TG and HDL-C, LDL-C, TC, TT, LH, FSH and PRL were compared between 2 groups before and after intervention. Results: The results of the study showed that after the MED/LC dietary pattern intervention, the patients' menstrual cycle recovery rate was 86.7%, which increased compared to 72.4%of patients in the LF group, and the difference was not statistically significant (P=0.174). Besides, BMI, WHR and BF% were significantly reduced, and serum or plasma levels of LH, LH/FSH, T, FPG, FINS, TG, TC, LDL-C and HOMA-IR and QUIKI indexes were significantly reduced after the MED/LC dietary intervention, with statistically significant differences compared to the LF group (P<0.05). Conclusions: The results of this study suggest that the MED/LC diet model is a good treatment for overweight PCOS patients, significantly restoring their menstrual cycle, improving their anthropometric parameters and correcting their disturbed endocrine levels, and its overall effectiveness is significantly better than the LF diet model.